PERBANDINGAN PENDAPATAN USAHATANI KANGKUNG VARIETAS NONA DENGAN USAHATANI KANGKUNG VARIETAS AINI DI KECAMATAN NARMADA KABUPATEN LOMBOK BARAT - Zulfiana, Ida; Muhsin, Muhsin; Mappanganro, Nurlailah (Teknosains: Media Informasi Sains dan Teknologi, 2023)
Kangkung (Ipomoeae aquatica) is one of the most popular vegetable horticultural plants because of its delicious taste, especially by people in Indonesia. Kangkung is widely cultivated in the West Nusa Tenggara area, especially in West Lombok Regency because the irrigation land is sourced directly from the Mount Rinjani springs in the area. Kangkung varieties that are cultivated on the island of Lombok are the Aini variety and the Miss variety. The purpose of this study was to determine the income, income differences, and constraints on kangkung farming of the Nona variety and the Aini variety in Narmada District, West Lombok Regency. This study uses a qualitative descriptive method that solves problems at the present time by collecting, compiling and analyzing and interpreting data, then drawing conclusions. The results obtained are: the amount of income in the Nona variety of kale farming is Rp. 69,648,240,-/, and for farming of kale Aini variety of Rp. 62.779,200,-/. So that there is a difference in the income of the Nona variety of water spinach farming with the Aini variety of kale, which is caused by the difference in production costs between the Nona variety of kale farming and the Aini variety of kale farming. Based on statistical analysis with t-test, there was no significant difference between the income of the Nona variety and the Aini variety. There are obstacles faced by the Nona variety of water spinach farming and the Aini variety of water spinach farming, namely capital, fertilizer. Keywords: Farming, Kangkung Variets Aini an Nona